Tumor Microenvironment Characterization in Breast Cancer and an Immune Cell Infiltration Score Development, Validation, and Application - Li, Lang (Frontiers in Oncology, 2022)
Abstract The tumor microenvironment (TME) refers to the cellular environment in which tumors exist. An increasing number of reports have emphasized its role in tumor progression, prognosis, relapse, metastasis, and therapeutic response with breast cancer (BRCA). Few studies have revealed a systematic landscape of immune cell infiltration (ICI) in BRCA. In this study, we comprehensively analyzed the immune cells infiltrating TME in BRCA. Three ICI patterns were identified through an unsupervised clustering method and an ICI score was developed by a principal component analysis (PCA). A Kaplan-Meier survival with log-rank test revealed a significant overall survival (OS) difference of BRCA patients with these three ICI patterns. We also found that a high ICI score was characterized by an elevated tumor mutation burden (TMB), effector T-cell infiltration, INF-γ-related cytotoxicity, and cytolytic activity score. An independent cohort validated that this ICI score could be a prognostic indicator for BRCA. Two immunotherapeutic cohorts and two chemotherapeutic cohorts confirmed that patients with higher ICI scores showed significant chemotherapeutic and immunotherapeutic advantages. In summary, these results suggest that the ICI patterns could act as a prognostic indicator and that the ICI score could precisely predict the clinical outcome for BRCA patients.